The Role of Tax Consultants as a Means in Raising Public Awareness to Paying Taxes in the Era of the Self Assessment System - Agus Salim; Mawaddah Irham (Penerbit Jurnal Indonesia, 2023)
The main objectives of this research are to find out the role of the tax consultant of Sahabat Mulia Binjai in managing the taxpayer self-assessment system, and to find out how far the role of the tax consultant of Sahabat Mulia is in attracting the interest of the local community to pay taxes. This study used descriptive qualitative method. Data collection techniques used are interviews, observation and documentation. The results of the study show that tax consultants play an important role as a means of making people aware of paying taxes in this era of the self-assessment system. Because the existence of a tax consultant who provides programs and campaigns makes the public more educated about understanding tax reporting and payment.